2014
DOI: 10.1007/s11060-014-1386-5
|View full text |Cite
|
Sign up to set email alerts
|

The pituitary stalk effect: is it a passing phenomenon?

Abstract: Most patients with large pituitary tumors do not exhibit hyperprolactinemia as a result of pituitary lactotroph disinhibition (stalk effect). Studies have demonstrated that increased intrasellar pressure is associated with both "stalk effect" hyperprolactinemia and pituitary insufficiency. Our primary hypothesis was that, despite continued disinhibition, lactotroph failure is responsible for normoprolactinemia in patients with large macroadenomas. As a corollary, we proposed that the hyperprolactinemia phase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…This translated in a decreased rate of recovery of pituitary function. Previous studies in patients with pituitary adenomas and stalk syndrome demonstrated an association of normal or elevated serum PRL levels with postoperative recovery from neuro-endocrine deficits [23][24][25][26][27]. With this in mind, we suggest that PRL levels may be helpful for the clinical decision making in patients with pituitary apoplexy, whereas unmeasurable to lower-than-normal values will predict panhypopituitarism and elevated levels may result in neuro-endocrine recovery.…”
Section: Corticotroph Insufficiencymentioning
confidence: 75%
“…This translated in a decreased rate of recovery of pituitary function. Previous studies in patients with pituitary adenomas and stalk syndrome demonstrated an association of normal or elevated serum PRL levels with postoperative recovery from neuro-endocrine deficits [23][24][25][26][27]. With this in mind, we suggest that PRL levels may be helpful for the clinical decision making in patients with pituitary apoplexy, whereas unmeasurable to lower-than-normal values will predict panhypopituitarism and elevated levels may result in neuro-endocrine recovery.…”
Section: Corticotroph Insufficiencymentioning
confidence: 75%
“…PRL levels caused by this effect do not seem to correlate with tumor size, stalk deviation, or the degree of stalk compression (6,21). In prolactinoma, there is a correlation between PRL levels and tumor size with macroprolactinoma (>10 mm in diameter) typically being associated with PRL levels >250 mg/L (12,17,22).…”
Section: Discussionmentioning
confidence: 97%
“…A possible explanation may be the "pituitary stalk effect"-defined by an elevation of PRL caused by the decrease of dopaminergic inhibition of lactotrophs associated with elevated intrasellar pressure by a nonePRL-secreting pituitary tumor (6).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperprolactinaemia is seen in 21% of ESSPA [17] and in 15% of the empty sella syndromes [1]. Some authors suggest it is due to the stalk effect observed in the intrasellar hypertension and consists of impaired dopamine delivery [1,3]. Continuity of the pituitary stalk is essential for adequate development and well-functioning of the pituitary gland [8].…”
Section: Discussionmentioning
confidence: 99%